Persepsi Penggiat Filsafat Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) terhadap Dimensi Religiusitas - Asyadily, Muhamad Hasan (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
The presence of philosophy in society is still widely questioned because it is considered capable of undermining beliefs, leading astray, and even having no benefits. The negative view of society towards philosophy is due to the religious and devout culture of the community. However, the development of education, especially at State Islamic Higher Education Institutions (PTKIN) and the establishment of Aqidah and Islamic Philosophy Department, it has given rise to philosophers within the student community at PTKIN. Moreover, the unique behavior of philosophy enthusiasts often attracts attention within the PTKIN student community, prompting researchers to examine the perceptions of philosophy enthusiasts regarding the dimension of religiosity in the midst of Indonesia's predominantly religious and devout cultural environment. This research employs a qualitative approach using Glock and Stark's theory on the dimensions of religiosity. The results show that the perceptions of philosophy activists at PTKIN regarding religiosity encompass three aspects. First, of aqidah, philosophy activists may become doubtful about their beliefs or, conversely, strengthen their faith, as well as cleanse impure religious doctrines. Second, in terms of worship, the non-performance of religious rituals is not solely caused by philosophy, but there are other factors at play. Third, morality or akhlak, philosophy has a positive impact on the behavior of philosophy activists.